Nomenclatural notes on some taxa of Bidessus Sharp and designation of a neotype (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) - Fery, Hans (Zootaxa, 2019)
The nomenclature of some taxa of the tribe Bidessini is dealt with. Currently, the names of these taxa are mostly interpreted as synonyms of Bidessus unistriatus (Goeze, 1777). The four oldest names for this species are shown to be nomina dubia due to insufficient descriptions and lack of name-bearing types. These names are in their original combinations Dyticus parvulus O.F. Müller, 1776, Dytiscus unistriatus Goeze, 1777, Dytiscus unistriatus Schrank, 1781, and Dyticus monostriatus Geoffroy in Fourcroy, 1785. The uncertainties of these species-level names also affect the identity of the genus-level names Bidessus Sharp, 1882, and Hydroglyphus Motschulsky, 1853a, meaning that the stability of nomenclature in the tribe Bidessini is considerably threatened. To eliminate this threat by clarifying the taxonomic status and the type locality of each of these nominal taxa, one and the same male specimen is designated as neotype for unistriatus Goeze, unistriatus Schrank and monostriatus Geoffroy in Fourcroy, and thus these three names become objective synonyms. The neotype is selected from modern material collected near Paris (France) because the type localities of all three taxa include "Paris environs". This is the locality from which Geoffroy (1762) described the non-binominal "ditique à une seule strie" and to which is referred in the descriptions of the latter three taxa. To prevent the threat of the stability by the name parvulus O.F. Müller it is intended to make an application to the ICZN in order to suppress this name for the purpose of priority.